'Resilience is a strategic priority' : conceptual analysis of the European Union’s Global Strategy - Kärkkäinen, Jenni (2016)
The aim was to study how resilience is defined, which themes it linked to and how its relevance is reasoned in the Global Strategy for the European Union’s Foreign and Security Policy (EUGS). The concept is generally connected to facing risk and adversity and therefore it was intriguing that it is employed over 30 times in the less than 60 pages of the strategy. Pragmatic turn in social sciences was one possible way to explain the rise of resilience in politics. There are already several articles written on the EUGS and resilience as its strategic priority, but they have studied these questions.